FORMING OF CONSCIOUS ATTITUDE TOWARD OWN HEALTH FOR FUTURE SPECIALISTS ON PHYSICAL REHABILITATION - Maslov, Roman V. (Educological discourse, 2015)
In the article the theoretical and methodical aspects of forming of conscious attitude are examined toward an own health for future specialists on a physical rehabilitation. Essence is reflected, basic approaches are sent to maintenance and strengthening of health of personality. Innovative forms and methods that assist forming of conscious relation of personality to the own health are certain. Substantial connections and dependences, that exist between the state of health of man and his way of life, by the level of knowledge about a health, mood, relationships with other people, are exposed. The substantive provisions of physiology, psychology of man, sociology, other contiguous disciplines are considered, that in totality will allow to realize necessary technologies, that keep, strengthen a health, form conscious attitude toward an own health and appear in corresponding positive acts and actions of personality.